OPTIMALISASI PENCEGAHAN DEMENSIA PADA LANSIA DENGAN PERMAINAN KARTU NOSTALGIA (PAKARNO) - Maria Orizani, Chindy; Susila, Wahyu Dini Candra; Iswati, Iswati (PPM STIKES Adi Husada, 2024)
Introduction & Aim: According to WHO, dementia is a neurodegenerative syndrome that arises due to a chronic and progressive disorder accompanied by impaired multiple sublime functions such as calculation, learning capacity, language, and decision making. The number of people with dementia in Indonesia is 1.2 million and Indonesia is included in the top ten countries with the highest dementia in the world and Southeast Asia in 2020. The phenomenon that occurs in the field shows that the decline in cognitive function in the elderly has not received maximum treatment. This community service activity aims to apply the use of the Nostalgia Card Game (PAKARNO) to prevent dementia in the elderly. Method of Activity: Community service is carried out by conducting education, demonstration and redemonstration with the Nostalgia Card Game (PAKARNO) as a form of prevention of dementia in the elderly. The number of respondents was 30 elderly people who were members of the Elderly Posyandu. Results: The results of the Wilcoxon sign-rank test showed an increase in knowledge about dementia with a p-value of 0.03 and skills with a p-value of 0.01, as well as a chi-square test on increase attitudes with a p-value of 0.01. Discussion: The success of the Reminiscence therapy program through nostalgic card games (PAKARNO) memory management in the elderly with dementia cannot be separated from the ability to remember events or events in the past so that it makes the respondent's commitment to be able to carry out therapy properly.